2001
DOI: 10.1081/ja-100000230
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Hiv Risk Behaviors Between New and Long-Term Injection Drug Users

Abstract: The purpose of this study was to characterize the injection and sexual risk behaviors of a cohort of active drug injectors who have initiated injection within the past 4 years and to compare their behaviors with the risk behaviors of long-term injectors who have been injecting drugs since 1984. A stratified, network-based sample was used to recruit injection drug users from the streets in Miami-Dade, Florida. After screening for eligibility, which included a urine test to confirm current drug use, participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 24 publications
1
9
1
Order By: Relevance
“…Our study provides some evidence to suggest that excess mortality among IDUs is not delayed until later stages of a drug user's career; instead, these data argue against an introductory period of relative safety. The data are disturbingly consistent with data on rapidly increasing risks of blood‐borne infections [18] and risky behaviors [30] among recent‐onset IDUs. Such information on the temporality of IDU mortality and accelerators of IDU death allows health systems to better plan for acute and chronic care needs of populations with high IDU prevalence, alerts drug abuse treatment programs to potential clinical and emergency care needs of their clients [31] and offers insights into how risk reduction interventions might prevent mortality among IDUs.…”
Section: Discussionsupporting
confidence: 70%
“…Our study provides some evidence to suggest that excess mortality among IDUs is not delayed until later stages of a drug user's career; instead, these data argue against an introductory period of relative safety. The data are disturbingly consistent with data on rapidly increasing risks of blood‐borne infections [18] and risky behaviors [30] among recent‐onset IDUs. Such information on the temporality of IDU mortality and accelerators of IDU death allows health systems to better plan for acute and chronic care needs of populations with high IDU prevalence, alerts drug abuse treatment programs to potential clinical and emergency care needs of their clients [31] and offers insights into how risk reduction interventions might prevent mortality among IDUs.…”
Section: Discussionsupporting
confidence: 70%
“…A nested case-control design was used to identify a study sample of 488 participants who were part of an already enrolled group of 900 street-recruited regular users of heroin who were participating in a study of the transition to injection and risk factors for HIV (Chitwood, Comerford, Kitner, Palacios, and Sanchez, 2001;Chitwood, Comerford, and Sanchez, 2003;Chitwood et al, 2000;Kelly and Chitwood, 2003). A stratified network-based (snowball) sample (Watters and Biernacki, 1989) of 900 non-Hispanic White, African American, and Hispanic men and women were recruited between July 1997 and February 2000 from multiple communities in south Florida known for high drug use.…”
Section: Methodsmentioning
confidence: 99%
“…48 Other studies have shown that HIV risk for heroin sniffers can be significantly reduced if transition to injection is delayed or prevented by contact with such treatment. [49][50][51][52] A study involving street-recruited crack cocaine smokers concluded that intervention programs should target crack cocaine smokers to prevent transition to injection. 53 Nevertheless, interventions to reduce this transition are needed.…”
Section: Transition From Non-injection To Injection Drug Usementioning
confidence: 99%